Produção de celulase por fermentação submersa empregando resíduos agroindustriais para produção de etanol - Barros, Maria Aparecida (2011)
The concern with the growing consumption of fuel, coupled with the scarcity of raw materials and environmental pollution encourage the use of biotechnology in the production of biofuels. In this respect the interests of a modern biotechnology is the use of municipal waste, industrial and agricultural to clean up the environment and creating alternative products and technologies associated with the production of ethanol. This study aims to evaluate the production and use of biomass hydrolytic enzyme complex mixed cheese whey and cellulose for ethanol production. This paper presents the results of the joint production of the enzymes β - galactosidase and cellulase in means containing lactose and cellulose fermentation submerged times in different culture composition whey 60g / L, yeast extract 3g / L with salts (mean 1),whey 60 g / L, cellulose 20 g / L, yeast extract 3g / L with salts (mean 2), lactose 40 g / L, yeast extract 3g / L with salts (mean 3), lactose 40 g / L, cellulose20g / L, yeast extract 3g / L with salts (mean 4). Observed - a higher enzyme production in media 3means 4 being chosen as the best means of fermentation for enzyme production due to increased production of cellulase in relation to the mean 3. After the choice of means was assessed joint production of enzymes and studied the hydrolysis of cellulose and whey produced by the enzymatic extract produced by Trichoderma reesei and Aspergillus niger. The best time of enzyme production was found for 12h , hydrolysis stabilized at approximately 8 h, with the temperature for the hydrolysis of whey set a 37º C and hydrolysis of cellulose to 45º. It can be observed that the enzymes produced by Aspergillus niger showed higher capacity when compared with the hydrolytic enzyme complex from Trichoderma reesei. Hydrolysis carried out with the enzyme complexes was compared with acid hydrolysis of biomass from whey and cellulose and the pH adjusted to acid hydrolysis in 1. After the hydrolysis was performed with a fermentation hydrolysates and observed - a higher production of ethanol in complex enzyme hydrolysed with Aspergillus niger.